- #1

- 29

- 0

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter morenogabr
- Start date

- #1

- 29

- 0

- #2

lanedance

Homework Helper

- 3,304

- 2

[tex] f(x) = \sum_{n=1}^{\infty} a_n x^n [/tex]

as a general rule I woudl try & make teh summation powers of x equivalent. If the other subscripts are confusing why not try a variable change [itex] c_n = b_{n-2}[/itex] etc.

- #3

- 29

- 0

f(x) = e^x = \\sum_{n=0}^{\\infty} (1/n!)(x^n),

[/tex]

[tex]

g(x) = sin(x) = \\sum_{k=0}^{\\infty} ((-1)^k)/(2k+1)! * x^(2k+1)

[/tex]

latex not working??? maybe its clear enoug what im trying to show...

I need to use cauchy product theorem to obtain the first 3 terms of f(x)g(x).

So for g(x) I say m=2k+1, k=(m-1)/2, etc to achieve x^m but then the sum goes from m=1 to inf.

So if I leave x powers equal, the summations start at 0 for f(x) and 1 for g(x). But the theorem only gives

c_n=sum(from 0 to inf) a_(k) * b_(n-k) not sure if this would need to go from 1 to inf in my case or leave as 0?

- #4

Char. Limit

Gold Member

- 1,208

- 14

f(x) = e^x = \\sum_{n=0}^{\\infty} (1/n!)(x^n),

[/tex]

[tex]

g(x) = sin(x) = \\sum_{k=0}^{\\infty} ((-1)^k)/(2k+1)! * x^(2k+1)

[/tex]

latex not working??? maybe its clear enoug what im trying to show...

I need to use cauchy product theorem to obtain the first 3 terms of f(x)g(x).

So for g(x) I say m=2k+1, k=(m-1)/2, etc to achieve x^m but then the sum goes from m=1 to inf.

So if I leave x powers equal, the summations start at 0 for f(x) and 1 for g(x). But the theorem only gives

c_n=sum(from 0 to inf) a_(k) * b_(n-k) not sure if this would need to go from 1 to inf in my case or leave as 0?

[tex]

f(x) = e^x = \sum_{n=0}^{\infty} \frac{x^n}{n!}

[/tex]

[tex]

g(x) = sin(x) = \sum_{k=0}^{\infty} \frac{(-1)^k x^{2k+1}}{(2k+1)!}

[/tex]

Use this format for your latex, it's better.

Share: